Health care providers' knowledge, attitude and perceived stigma regarding tuberculosis in a pastoralist community in Ethiopia: a cross-sectional study - Bezawit Temesgen Sima; Tefera Belachew; Fekadu Abebe (BMC, 2019)
Abstract Background Tuberculosis (TB) remains the prime killer disease among infectious diseases. TB control depends on early case detection and treatment in a directly observed treatment short course (DOTS) programme. The success of DOTS depends on the ability of the health care system to identify and properly manage TB cases. The present study aims to assess healthcare provider (HCP) knowledge, attitude and perceived stigma regarding TB and perception about traditional healers. Methods A descriptive cross sectional study was conducted among 108 HCPs using a semi-structured, self-administered questionnaire from September 2014 to January 2015. The study district has a high TB burden area with one district hospital, 4 health centres, and 18 health posts. All health facilities and HCPs available during the study period in the district were included in the study. Statistical software for social science (SPSS) version 22 and STATA version 14 were used to enter and analyse data, respectively. Results The majority (64%) of the HCPs had poor overall knowledge regarding TB, and 67.6 and 57.6% had poor knowledge regarding TB diagnosis and nature of the disease, respectively. Moreover, most 66.7 and 55.6% of the HCPs had an unfavourable attitude towards TB and TB control systems, respectively. Slightly under half (49.1%) of the HCPs had a favourable attitude towards TB patients, and the majority (88.9%) had low perceived stigma. The majority (87.0%) of the HCPs indicated the importance of community involvement in TB control activity. Moreover, most (60.2%) of the HCPs showed willingness to collaborate with traditional healers (THs) on TB control activity. Conclusions Healthcare workers' knowledge gap and unfavourable attitude towards TB control systems reported in this study may cause poor TB care delivery. HCPs' perception of the importance of community involvement in TB control and willingness to collaborate with THs on TB management could be an opportunity to strengthen the World Health Organization's (WHO's) component of End TB strategy through community engagement. Training and workshops could be used to address the knowledge gap and the unfavourable attitude regarding TB among HCPs.